Applications of hurdles in the processing of snail (Achachatina marginata) meat - Eke, Mike O; Kukwa , R E (Journal of Postharvest Technology, 2022)
Inadequate protein consumption is one of the major challenges in most developing countries especially in Africa both to urban and rural  dwellers. Snail meat was processed into dried snails using salt, sugar and citric acid at different concentrations of 0.1% (B), 0.2% (C), 0.3%  (D), and 0.5% (E). The control sample (Sample A) was without treatment. Analyses of minerals, vitamins, proximate and anti-nutritional  properties were carried out using standard methods. All results showed statistical difference (P
Keywords: Storage fungi; Aspergillus flavus; , essential oils; growth inhibition